Adrenal Cyst Presenting as Hepatic Hydatid Cyst - Abdulla Darwish; Veena Nagaraj; Mohmmed B. Mustafa; Ahmed Al Ansari (Case Reports in Surgery)
Introduction. Although adrenal cysts are uncommon, the incidence rate is increasing with the advances in radiological technologies. The incidental detection of adrenal cysts nowadays has become more frequent as a result of the increase usage of high quality imaging modalities. Adrenal cysts originate from the adrenal gland and can be classified into either true or pseudocyst. Presentation of Case. In this report, we described an adrenal cyst of endothelial type, in a 30-year-old lady who was mistakenly diagnosed to have a hydatid cyst both clinically and by imaging. Discussion. Although adrenal cysts are uncommon, the incidence rate is increasing with the frequent use of various high quality radiological technologies. Adrenal cyst should be considered in the differential diagnosis when dealing with upper abdominal cysts. The size of the adrenal cyst can vary from a few millimeters up to 50 cm in diameter. Most of the adrenal cysts are unilateral, while 8%–15% of those cysts do present bilaterally. The majority of cases are diagnosed between the 3rd and 5th decades. Conclusion. Although most of the adrenal cysts are benign in nature, surgical excision is advisable especially when the cysts are greater than 5 cm in diameter and in the case of suspecting malignancy.